The Relationship Between Children's Health Status and Stunting in Toddlers at Mamboro Health Center, Palu - Suarayasa, Ketut; Miranti, Miranti; Ayu Wandira, Bertin (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Taipa Sub-District in Palu City has a high prevalence of stunting, with 24.7% or 108 cases out of 437 toddlers measured. This makes Taipa, located in the Mamboro Health Center area, the sub-district with the highest stunting cases in Palu City. This research aims to analyze the relationship between children's health status (exclusive breastfeeding, colostrum feeding, frequency of breastfeeding, and history of infectious diseases) and the incidence of stunting in the Mamboro Health Center working area. Methods: This quantitative study uses a case-control design to determine the magnitude of risk factors related to children's health status and the incidence of stunting in toddlers within the Mamboro Health Center working area. The total sample comprised 204 toddlers, including 102 stunted toddlers (cases) and 102 normal toddlers (controls). Results: There is a significant relationship between exclusive breastfeeding and a history of infectious diseases with the incidence of stunting in toddlers (p<0.05). Mothers who do not provide exclusive breastfeeding have a 2.2 times higher risk of their children being stunted (OR = 2.225). Children who have experienced infectious diseases have a 1.9 times higher risk of becoming stunted (OR = 1.944). However, the frequency of breastfeeding and colostrum feeding did not show a significant relationship with stunting among toddlers in the Mamboro Health Center working area. Conclusion: The child's health status factors that are significantly related to the incidence of stunting include exclusive breastfeeding and a history of infectious diseases. These findings highlight the need for interventions promoting exclusive breastfeeding and effective management of infectious diseases to reduce stunting rates in this area.